2023
DOI: 10.31004/joe.v5i4.2534
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of School Environment and Compensation on Performance of Vocational School Teachers

Abstract: This study's objective was to determine and evaluate the impact of compensation and the workplace on teachers' performance in private schools, involving 70 teachers. The survey method is used in this study. A questionnaire technique was used to collect data. Path analysis was used to examine the data. The study's findings indicate that there is a direct relationship between pay and teacher performance with a Sig. 0.00 < 0.05, a direct relationship between the work environment and teacher performance with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…This means that as the quality of school life for adolescent students improves, it leads to a reduction in learned helplessness and vice versa. This finding is consistent with the results of previous studies (Button et al, 2013;Erlianti et al, 2023;Fais, 2017;Johnson et al, 2011;Kelly et al, 2016;Larashati et al, 2022;Lee et al, 2020;Li et al, 2011;Maba, 2022;Moreland et al, 2015;Oladele, 2014;Prihadi et al, 2018;Raufelder & Kulakow, 2021;Salminen et al, 2014;Wei & Chen, 2022;Wu & Tu, 2019;Yoong et al, 2015), suggesting that school life quality is an effective factor in reducing learned helplessness. These studies found that improving the quality of life for adolescent girls leads to better stress management and challenging situations, thereby reducing learned helplessness.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This means that as the quality of school life for adolescent students improves, it leads to a reduction in learned helplessness and vice versa. This finding is consistent with the results of previous studies (Button et al, 2013;Erlianti et al, 2023;Fais, 2017;Johnson et al, 2011;Kelly et al, 2016;Larashati et al, 2022;Lee et al, 2020;Li et al, 2011;Maba, 2022;Moreland et al, 2015;Oladele, 2014;Prihadi et al, 2018;Raufelder & Kulakow, 2021;Salminen et al, 2014;Wei & Chen, 2022;Wu & Tu, 2019;Yoong et al, 2015), suggesting that school life quality is an effective factor in reducing learned helplessness. These studies found that improving the quality of life for adolescent girls leads to better stress management and challenging situations, thereby reducing learned helplessness.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, school quality of life is one of the most significant factors affecting adolescents' mental health. School quality of life, a concept that can be enhanced through the design of educational methods, reflects the level of students' satisfaction with their daily life in school (Erlianti et al, 2023;Maba, 2022;Oladele, 2014;Raufelder & Kulakow, 2021). It impacts both formal and informal aspects of school and is influenced by society, individual experiences, and peer relationships (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation